1920 թ. մայիսի 7-ի ռուս-վրացական դաշնագիրը և Բաթումի հանձնումը Վրաստանին - Թորոսյան Շիրակ (YSU Journal of International Affairs, 2016)
One of the most important issues in the foreign policy of the First Republic of Armenia was the question of the access to the sea, and one of the possible solutions to this issue the Batumi port was considered. This article addresses the issue of Batumi in the context of the Armenian-Georgian, Russian-Georgian, AngloRussian and Kemalo-Bolshevik relations. According to the agreement signed between Soviet Russia and Menshevik Georgia on 7 May of 1920, the Bolsheviks recognized the Batumi region as an integral part of Georgia, in return for which the Mensheviks promised to withdraw the British garrison from there. On July 7, the British handed over the command of Batumi to Georgia and left this place. Armenia’s interests were again ignored, as the British did not fulfill their promise regarding the declaration of Batumi free port. However, in the Treaty of Sevres, there was referred to the status of Porto franco for Batumi. At the end of 1920 and beginning of 1921, there were contradictions between the Kemalists and Bolsheviks with respect to Batumi. In the end, Russia insisted on that Batumi should receive the status of the territory of the Soviet Georgia, which was recorded in the Moscow Treaty of March 16, 1921. During the Lausanne Conference, which revised the Treaty of Sevres there was said nothing regarding Batumi. Thus, the right of Armenia to have access to the sea was grossly violated.